Analisis Faktor - Faktor Yang Mempengaruhi Minat Mahasiswa Akuntansi Kota Batam Dalam Pengambilan Keputusan Investasi - Hidayah, Wulan; Banjarnahor, Haposan (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
This study aims to analyze the factors that influence the interest of accounting students in Batam City in making investment decisions. The main variables studied include financial socialization, overconfidence, and mental accounting. Quantitative methods with a survey approach and statistical testing through SPSS are used to measure the influence of each variable on students' investment interest. The results of the analysis show that the three variables partially and simultaneously have a positive and significant effect on students' interest in capital market investment. This finding confirms that financial knowledge obtained from socialization, overconfidence, and mental financial management play a major role in motivating students to invest. The results of this study are expected to be a reference in designing more effective financial education strategies and increasing students' literacy and interest in the world of investment, in order to support local and national economic growth in the future.